The biology learning process in class XI of IPA 1 of MAN 2 Kabupaten Tebo, was still teacher-centered. The learning methods which were used less varied. It made the students got low activities and competence in learning. There were still many students who - Simbolon, Perima; Anhar, Azwir; advinda, linda (Kolaboratif, 2014)
Available instructional materials of entomology are complicated and boring presentation. It can contribute toward to the low studentsâ€™ ready interest. Teaching materials are an important medium in the learning process. Lecturers as implementing education should strive to plan and construct a teaching material. One of the teaching materials that can be developed is a module. This study aims to develop a module that is valid, practical, and effective for entomology lectures. This research is the development of a model by using 4-D. This model consists of four stages: define, design, develop, and disseminate. At this stage of analysis define the curriculum, concepts, and students. This stage is to design module. At the stage of develop is test the validity and the practicalities of modules. At this stage of disseminate is to testÂ the effectiveness. Modules that have been designed validated by five validators. Once the module is valid, its practicalities tested modules to two lecturers and students of the semester VIC Biology Education STKIP South Tapanuli Padangsidimpuan. Test conducted to is see the effectiveness of motivation, activity and student learning outcomes. Data were collected by questionnaires effectiveness motivation, observation sheets, and tests on students. The results of this research is the development of a product in the form of mind map-based module entomology for students of biology education. Modules developed have met validity aspects, practicalities, and effectiveness. The value aspect of the validity of the module is very valid category 84.2%, 91.1% practicalities very practical category, 87.9% category learning activity is very effective, 90.5% category learning motivation is very high motivation, and learning outcomes on average 80, 0 categories graduation. Based on the mean value of the module that was developed is feasible to use in lectures, the module provides convenience to faculty and students, improve learning activity, student motivation and learning outcomes.